Global histone protein surface accessibility in yeast indicates a uniformly loosely packed genome with canonical nucleosomes - Marr, Luke T. (2021)
Background: The vast majority of methods available to characterize genome-wide chromatin structure exploit differences in DNA accessibility to nucleases or chemical crosslinking. We developed a novel method to gauge genome-wide accessibility of histone protein surfaces within nucleosomes by assessing reactivity of engineered cysteine residues with a thiol-specific reagent, biotin-maleimide (BM). Results: Yeast nuclei were obtained from cells expressing the histone mutant H2B S116C, in which a cysteine resides near the center of the external flat protein surface of the nucleosome. BM modification revealed that nucleosomes are generally equivalently accessible throughout the S. cerevisiae genome, including heterochromatic regions, suggesting limited, higher-order chromatin structures in which this surface is obstructed by tight nucleosome packing. However, we find that nucleosomes within 500 bp of transcription start sites exhibit the greatest range of accessibility, which correlates with the density of chromatin remodelers. Interestingly, accessibility is not well correlated with RNA polymerase density and thus the level of gene expression. We also investigated the accessibility of cysteine mutations designed to detect exposure of histone surfaces internal to the nucleosome thought to be accessible in actively transcribed genes: H3 102, is at the H2A–H2B dimer/H3–H4 tetramer interface, and H3 A110C, resides at the H3–H3 interface. However, in contrast to the external surface site, we find that neither of these internal sites were found to be appreciably exposed. Conclusions: Overall, our finding that nucleosomes surfaces within S. cerevisiae chromatin are equivalently accessible genome-wide is consistent with a globally uncompacted chromatin structure lacking substantial higher-order organization. However, we find modest differences in accessibility that correlate with chromatin remodelers but not transcription, suggesting chromatin poised for transcription is more accessible than actively transcribed or intergenic regions. In contrast, we find that two internal sites remain inaccessible, suggesting that such non-canonical nucleosome species generated during transcription are rapidly and efficiently converted to canonical nucleosome structure and thus not widely present in native chromatin.